Prognostic Value of Volume-Based Parameters Measured by SSTR PET/CT in Neuroendocrine Tumors: A Systematic Review and Meta-Analysis - Hou, Jiale; Yang, Yi; Chen, Na; Chen, Dengming; Hu, Shuo (Frontiers in Medicine, 2021)
Purpose: A meta-analysis was conducted to investigate the value of the volume parameters based on somatostatin receptor (SSTR)-positron emission tomography (PET) in predicting the prognosis in patients with neuroendocrine tumors (NETs). Material: PUBMED, EMBASE, Cochrane library, and Web of Knowledge were searched from January 1990 to May 2021 for studies evaluating prognostic value of volume-based parameters of SSTR PET/CT in NETs. The terms used were “volume,” “positron emission tomography,” “neuroendocrine tumors,” and “somatostatin receptor.” Pooled hazard ratio (HR) values were calculated to assess the correlations between volumetric parameters, including total tumor volume (TTV) and total-lesion SSTR expression (TL-SSTR), with progression-free survival (PFS) and overall survival (OS). Heterogeneity and subgroup analysis were performed. Funnel plots, Begg's and Egger's test were used to assess possible underlying publication bias. Results: Eight eligible studies involving 593 patients were included in the meta-analysis. In TTV, the pooled HRs of its prognostic value of PFS and OS were 2.24 (95% CI: 1.73–2.89; P < 0.00001) and 3.54 (95% CI, 1.77–7.09; P = 0.0004), respectively. In TL-SSTR, the pooled HR of the predictive value was 1.61 (95% CI, 0.48–5.44, P = 0.44) for PFS. Conclusion: High TTV was associated with a worse prognosis for PFS and OS in with patients NETs. The TTV of SSTR PET is a potential objective prognosis predictor.